Heterogeneous Histories of Recombination Suppression on Stickleback Sex Chromosomes. (12th June 2021) - Sardell, Jason M; Josephson, Matthew P; Dalziel, Anne C; Peichel, Catherine L; Kirkpatrick, Mark
Abstract: How consistent are the evolutionary trajectories of sex chromosomes shortly after they form? Insights into the evolution of recombination, differentiation, and degeneration can be provided by comparing closely related species with homologous sex chromosomes. The sex chromosomes of the threespine stickleback ( Gasterosteus aculeatus ) and its sister species, the Japan Sea stickleback ( G. nipponicus ), have been well characterized. Little is known, however, about the sex chromosomes of their congener, the blackspotted stickleback ( G. wheatlandi ). We used pedigrees to obtain experimentally phased whole genome sequences from blackspotted stickleback X and Y chromosomes. Using multispecies gene trees and analysis of shared duplications, we demonstrate that Chromosome 19 is the ancestral sex chromosome and that its oldest stratum evolved in the common ancestor of the genus. After the blackspotted lineage diverged, its sex chromosomes experienced independent and more extensive recombination suppression, greater X–Y differentiation, and a much higher rate of Y degeneration than the other two species. These patterns may result from a smaller effective population size in the blackspotted stickleback. A recent fusion between the ancestral blackspotted stickleback Y chromosome and Chromosome 12, which produced a neo-X and neo-Y, may have been favored by the very small size of the recombining region on the ancestral sex chromosome. We identify six strata on the ancestral and neo-sex chromosomes where recombination between the X and Y ceased at different times. These results confirm that sex chromosomes can evolve large differences within and between species over short evolutionary timescales.